Efforts to Improve Student Learning Outcomes through the Card Sort Method in Islamic Education Learning at SD Negeri Pandan Sari Gunung Meriah - Suswanti; Suryati (Journal of Indonesian Primary School, 2025)
This study aims to test the effectiveness of the Card Sort method in improving student learning outcomes in Islamic Education at SD Negeri Pandan Sari Gunung Meriah. This study used a quantitative approach with a pre-test and post-test design to assess changes in student understanding and performance before and after the intervention. The results showed a significant increase in student performance, with the average post-test score increasing from 55% to 75%. The Card Sort method helped students develop a deeper understanding of key Islamic concepts such as prayer, zakat, fasting, and the five pillars of Islam by actively engaging them in categorizing and sorting related materials. In addition to improved academic performance, students showed increased engagement, motivation, and collaboration. This method also encouraged critical thinking and problem-solving skills. The role of the teacher in guiding the activity was essential to maintain focus and ensure meaningful learning. Although there were challenges with full student engagement, the overall results showed that the Card Sort method was an effective strategy to improve student learning in Islamic Education. This study highlights the importance of an interactive and student-centered learning approach in fostering a more dynamic and engaging classroom environment.